A Role for the Parietal Cortex in Sensorimotor Adaptation of Saccades. (5th October 2012) - Panouillères, Muriel; Habchi, Ouazna; Gerardin, Peggy; Salemme, Romeo; Urquizar, Christian; Farne, Alessandro; Pélisson, Denis
Abstract : Sensorimotor adaptation ensures movement accuracy despite continuously changing environment and body. Adaptation of saccadic eye movements is a classical model of sensorimotor adaptation. Beside the well-established role of the brainstem–cerebellum in the adaptation of reactive saccades (RSs), the cerebral cortex has been suggested to be involved in the adaptation of voluntary saccades (VSs). Here, we provide direct evidence for a causal involvement of the parietal cortex in saccadic adaptation. First, the posterior intraparietal sulcus (pIPS) was identified in each subject using functional magnetic resonance imaging (fMRI). Then, a saccadic adaptation paradigm was used to progressively reduce the amplitude of RSs and VSs, while single-pulse transcranial magnetic stimulation (spTMS) was applied over the right pIPS. The perturbations of pIPS resulted in impairment for the adaptation of VSs, selectively when spTMS was applied 60 ms after saccade onset. In contrast, the adaptation of RSs was facilitated by spTMS applied 90 ms after saccade initiation. The differential effect of spTMS relative to saccade types suggests a direct interference with pIPS activity for the VS adaptation and a remote interference with brainstem–cerebellum activity for the RS adaptation. These results support the hypothesis that the adaptation of VSs and RSs involves different neuronal substrates.